87.6k views
4 votes
What’s 6(2x-3) - 2(2x+1)

What’s 6(2x-3) - 2(2x+1)-example-1
User Questieme
by
7.3k points

2 Answers

1 vote
=(6 • 2x -6 • 3) - (2•2x +2)
=(12x -18) - (4x +2)
=12x -18 - 4x -2
=8x-20
User Kevin Regenrek
by
6.0k points
3 votes

Answer:

8x - 20

Explanation:

Simplifying the expressions:

6*(2x -3) - 2*(2x + 1)

Use distributive property to open the parenthesis. a*(b - c) =(a*b) - (a*c)

6*(2x -3) - 2*(2x + 1) = 6*2x - 6*3 -2*2x - 2*1

= 12x - 18 - 4x - 2

= 12x - 4x - 18 - 2

Combine the like terms.

12x and (-4x) are like terms. 12x - 4x = 8x

(-18) and (-2) are constants. -18 - 2 = -20

= 8x - 20

Answer: 8x - 20

User Vipin
by
8.2k points